A transnational double movement? Polanyian reflections on conflicts law constitutionalism - Steven Klein (European Law Open)
Few issues remain as fraught as the relationship between European integration and national welfare states. For too long, Social Europe was an afterthought, relegated to the soft domain of the open method of coordination, while the formation of the single market proceeded with the full force of European law and institutions. Since the 2008 financial crisis, the social has returned—not just in Europe, but in all regions grappling with what comes after neo-liberalism. In this response, I turn to Christian Joerges’s seminal articulation of the conflict of laws as Europe’s constitutional form as a contribution to this current theoretical task. Central here has been how Joerges has staged a dialogue between theories of European law and the critique of the market order developed by the Hungarian philosopher and social theorist Karl Polanyi. I argue that Joerges picks up on democratic undercurrents in Polanyi’s theory that move beyond the opposition between nationally bounded welfare states and transnational private economic rights. Rather, we can see the social as a domain of multi-level democratic conflict mediation. While Joerges respects the ordoliberal vision of an economic constitution, he draws attention to their democratic deficits. Indeed, both the ordoliberals and Polanyi would reject the EU’s technocratic instrumentalisation of the market as a device for restructuring national social systems in a way that both deformalises European law and undermines its democratic legitimacy. I conclude with some speculative remarks about how the EU could be seen as introducing new dimensions of conflict into an emerging post-neoliberal order.